Factors Influencing Employees' Work-Life Balance in Commercial Banks of Nepal: Evidence from Structural Equation Modeling (Quest Journal of Management and Social Sciences, 2023)
Purpose: Work-life balance is a phenomenon that has expanded worldwide and has long been a contentious subject because of its significant impact on job satisfaction, time management, stress management, and other important areas of people's daily lives. This study aims to assess factors influencing employees' work-life balance in the commercial banks of the Kathmandu Valley.Design/ Methodology: We used descriptive and inferential statistics to statistically assess the data collected through structured questionnaires in line with the explanatory study design to examine the cause-and-effect connection. The Kathmandu Valley's 264 commercial bank employees' data are collected, and structural Equation Modeling (SEM) is used to evaluate it. We used the 5-point Likert scale as the primary data collection method in KOBO Toolbox.Findings: Findings reveal that most of the respondents working in the commercial bank are female and have completed a master’s degree and above educational level. The SEM result indicates that personal and organizational predictors and life satisfaction significantly relate to work-life balance. In contrast, life satisfaction mediates between dependent variables (Work-Life Balance) and independent variables (i.e.personal predictors and organizational predictors).Conclusion: There is no flexible time for work in commercial banks. The study shows long working hours, whereas most employees face challenges because of working conditions. Thus, commercial banks should reduce work pressure, maintain a positive working environment, and discourage overtime culture to improve work-life balance.Recommendation: The study recommends schedule flexibility, reducing workload and revising organizational policies to enhance work-life balance.